Determination Of Residual Bromopropylate And Its Degradation Product In Honey And Wax Against Varroa Infestation In Bees - A. Nasim (Pakistan Journal of Science, 2010)
A mite infestation control product bromopropylate was used over a 2 year period (1990 - 1992) to control Varroa jacobsoni infestation by means of colony treatment in autumn. Treatments were given to 12 hives located in the hilly areas of Islamabad and Murree. The residual levels of Bromopropylate and its degradation product were measured in the honey and wax. The samples were taken from each hive in March, May, July and August in the year following treatment. Chemical Analysis via gas chromatography showed that bromopropylate persisted in wax samples, bromopropylate were present in honey samples.